SPONTANEOUS VISUAL RECOVERY FOLLOWING COMBINED CENTRAL RETINAL VEIN AND CILIORETINAL ARTERY OCCLUSION – CASE REPORT - Sekerinov, Natasa Trpevska; Petrusevska, Andrijana; Dastevska, Emilija Gjosevska (Journal of Morphological Sciences; Vol 6 No 3 (2023): JMS, 2023)
Combined central retinal vein occlusion and cilioretinal artery occlusion is a rare variant of retinal vascular disease, which causes sudden unilateral visual acuity loss. The most important risk factors are the same as those for atherosclerosis (advanced age, hypertension, hyperlipidemia, diabetes, cigarette smoking, positive family history). The purpose of this paper is to describe Ð° 41-year-old patient with reduced vision in the right eye with this condition, who had spontaneous improvement in visual acuity. Keywords :   central retinal vein occlusion; cilioretinal artery occlusion; spontaneous visual recovery.